Spinal Tumors and Outcomes of Surgical Treatment: A Retrospective Study - Temiz, Çağlar; Kural, Cahit; Kırık, Alpaslan; Pusat, Serhat; Seçer, Halil İbrahim; Gönül, Engin; İzci, Yusuf (Fırat University, 2011)
Objective: Since many years, spinal tumors became the focus of interest of neurosurgery because of low morbidity rate and successfull outcome is obtained when the early diagnosis and appropriate surgical methods are applied. In this study, we aimed to document our experience and clinical outcomes on spinal tumors over a 10-year period. Materials and Methods: Ninety-four patients with spinal tumors who underwent surgical treatment between 1999 and 2008 are investigated retrospectively according to age and sex, presentation symptoms, neurological findings at admission, localizations, surgical techniques, resection types, pathological diagnosis, early surgical results, adjuvant therapies such as chemotherapy and radiotherapy, follow-up outcomes and surgical complications. Results: 77.65% of all cases were primary spinal tumors and 46.8% of the cases were located extradurally. Metastatic tumors were low than the primary tumors. Epandymomas were the most common tumors primary spinal tumors and located frequently in the lumbar region. The most common metastatic tumor was the lung carcinoma. The clinical outcomes were worse in patients who had a short time period between the initiation of the symptoms and admission. Neurological improvement was better in patients who had partial neurological loss at admission when compared with the patients who had complete neurological loss. The outcomes were worse in patients with metastatic tumors and intramedullary tumors, while better outcomes were obtained in patients with meningioma, ependymoma and schwannoma. Conclusion: Spinal tumors are the lesions which required early diagnosis and prompt surgical intervention. Intradural localization is gradually increased and primary spinal tumors get ahead of metastasis.

Amaç: Spinal tümörler düşük morbidite oranları ve erken tanı ve uygun tedavi metodları uygulandığında olumlu sonuçlar alınması nedeni ile nöroşirürjinin uzun yıllardır ilgi odağı olmuştur. Teknolojik ilerlemeye paralel olarak tanı olanaklarının artması ve mikrocerrahinin gelişimi ile başarı oranları artmıştır. Bu çalışma ile kliniğimizin spinal tümörlerdeki 10 yıllık tecrübesini ve klinik sonuçlarını ortaya koymayı amaçladık. Gereç ve Yöntem: 1999–2008 yılları arasında ameliyat edilen spinal tümörlü 94 olgu retrospektif olarak incelenerek hastaların yaş ve cins dağılımları, başvuru semptomları, başvuru anındaki nörolojik muayene bulguları, yerleşim yerleri, cerrahi girişim şekilleri, tümörlerin cerrahi olarak çıkartılma miktarları, patoloji sonuçları, erken cerrahi sonuçlar, cerrahi sonrasında hastalara radyoterapi ve kemoterapi uygulanıp uygulanmaması, hastaların izlem sonuçları ve cerrahi komplikasyonlar incelenmiştir. Bulgular: Tüm spinal tümörlerin %77,65'inin primer spinal tümör olduğu ve %46,8'inin ekstradural olduğu saptanmıştır. Serimizde metastatik spinal tümörler primer tümörlere daha az orandadır. Epandimomalar en sık görülen primer spinal tümörler olup en sık lomber bölgede yerleşmişlerdir. En sık görülen metastatik tümör akciğer kanseridir. Yakınma ile başvuru arasında geçen sürenin kısa olduğu hastalarda sonuçlar, uzun olan hastalara göre daha kötü olarak bulunmuş ve prognozu etkileyen faktörlerden biri olarak görülmüştür. Cerrahi sonrasında nörolojik düzelmenin, kısmi nörolojik kayıplı hastalarda en çok, tam nörolojik kayıplı hastalarda ise en az olduğu gözlenmiştir. Cerrahi sonrasında metastatik tümörlerde ve intramedüller tümörlerde sonuçlar daha kötü iken meningioma, schwannomalar ve epandimomalarda oldukça yüksek oranda düzelme gözlenmiştir. Sonuç: Spinal tümörler erken tanı ve çabuk cerrahi müdahale gerektiren lezyonlardır. İntradural yerleşim oranı giderek artmakta ve primer tümörler metastazların önüne geçmektedir.
Spinal Tümörler ve Cerrahi Tedavi Sonuçları: Retrospektif Çalışma